Comprehensive Assessment of Quality of Life, Functioning, and Mental Health in Children With Juvenile Idiopathic Arthritis and Noninfectious Uveitis. Issue 8 (8th June 2022) - McDonald, Joseph; Cassedy, Amy; Altaye, Mekibib; Andringa, Jennifer; Cooper, Ashley M.; Drews‐Botsch, Carolyn; Engelhard, George; Hennard, Theresa; Holland, Gary N.; Jenkins, Kirsten; Lambert, Scott R.; Lipscomb, Jessi; et al.
Abstract : Objective: Pediatric uveitis can lead to sight‐threatening complications and can impact quality of life (QoL) and functioning. We aimed to examine health‐related QoL, mental health, physical disability, vision‐related functioning (VRF), and vision‐related QoL in children with juvenile idiopathic arthritis (JIA), JIA‐associated uveitis (JIA‐U), and other noninfectious uveitis. We hypothesized that there will be differences based on the presence of eye disease. Methods: A multicenter cross‐sectional study was conducted at four sites. Patients with JIA, JIA‐U, or noninfectious uveitis were enrolled. Patients and parents completed the Pediatric Quality of Life Inventory (PedsQL; health‐related QoL), the Revised Childhood Anxiety and Depression Scale (RCADS; anxiety/depression), the Childhood Health Assessment Questionnaire (C‐HAQ; physical disability), and the Effects of Youngsters' Eyesight on Quality of Life (EYE‐Q) (VRF/vision‐related QoL). Clinical characteristics and patient‐reported outcome measures were compared by diagnosis. Results: Of 549 patients, 332 had JIA, 124 had JIA‐U, and 93 had other uveitis diagnoses. Children with JIA‐U had worse EYE‐Q scores compared to those with JIA only. In children with uveitis, those with anterior uveitis (JIA‐U and uveitis only) had less ocular complications, better EYE‐Q scores, and worse C‐HAQ and PedsQL physical summary scores compared to those with nonanterior disease. In children with anterior uveitis, those with JIA‐U had worse PedsQL physical summary and C‐HAQ scores than anterior uveitis only. Further, EYE‐Q scores were worse in children with bilateral uveitis and more visual impairment. There were no differences in RCADS scores among groups. Conclusion: We provide a comprehensive outcome assessment of children with JIA, JIA‐U, and other uveitis diagnoses. Differences in QoL and function were noted based on underlying disease. Our results support the addition of a vision‐specific measure to better understand the impact of uveitis.